Integrated Hydrodynamic Modeling of Dam Failure and Downstream Flood Inundation near Kathmandu, Nepal using MIKE Hydro River Model - Kuldeep Pareta (Journal of Hydraulic Structures)
The integrated hydrodynamic modeling study conducted in the Kathmandu valley, Nepal, utilizing the MIKE Hydro River Model and incorporating diverse datasets, including satellite imageries, ALOS PALSAR RTC DEM data, topographical map at 1:25,000 scale and hydraulic data. Various scenarios, including a probable maximum flood (PMF) routing simulation, were examined, with a focus on assessing impacts on infrastructure, particularly two bridges located at different chainages. The analysis uncovered that the invert level at bridge-1 measured 1384.19 meters, while at bridge-2, it was recorded at 1343.98 meters. Historical records show significant floods in various years, including 1988, 1991, 1995, 1996, 1999, 2018, 2019, 2021, 2022, and 2023. During the flood inundation modeling, it was observed that the water level of the river near Gokarneshwar Mahadev and its adjacent areas experienced an elevation increase to 13 meters. Furthermore, the water level near both modeled bridges was noted to rise to 8 meters. Conversely, in other segments of the modeled river, the water level ranged between 5 to 6 meters. Hydrodynamic modeling emerged as a critical tool for flood risk assessment, providing accurate simulations of water flow behavior and facilitating informed decision-making for flood risk management and infrastructure resilience.